Population declines among Canadian vertebrates: But data of different quality show diverging trends. (November 2021) - Marconi, Valentina; McRae, Louise; Müller, Helen; Currie, Jessica; Whitmee, Sarah; Gadallah, Fawziah (ZuZu); Freeman, Robin
Highlights: We produced a biodiversity indicator for Canada based on the Living Planet Index. It includes over 3000 abundance time-series for more than 50% of native vertebrates. Abundance declined by 10% on average 1970–2014, with trends varying across taxa. Low-quality data show declining trends, high-quality ones are increasing. Abstract: We produced a biodiversity indicator, the Canadian Species Index (CSI), by gathering abundance data for Canadian vertebrate populations and adapting the Living Planet Index methodology. The final indicator incorporates over 3000 abundance time series and contains data for more than 50% of Canadian native vertebrate species. Species abundance declined by an average 10% between 1970 and 2014, with trends varying across taxonomic groups. To facilitate the interpretation of the indicator and contribute to the transparency of the reporting process, here we present a discussion of the indicator's coverage, data quality and data gaps. Using data collected for other purposes means the dataset inherits the biases in biodiversity monitoring. We therefore assessed taxonomic and geographic coverage of the data underlying the indicator to highlight which areas and groups are under-represented. Birds are comprehensively monitored across Canada and are considered good indicators of the state of the environment. Other taxonomic groups are less well monitored, and the data available for these groups often consist of shorter and less full time series, representing smaller segments of the national population. A disaggregation based on data quality appears to show that trends based on species with lower quality data are more negative than for species with higher quality data. We discuss possible sources of the difference, including the relationship between taxon and data quality. Additional data collection on species contributing to the lower-quality subsets is needed to confirm negative trends.